Encontros na escola : afecções adolescentes - Penteado, Helena de Arruda (2013)
This study aimed to ascertain the conditions - in the philosophical sense of the concept based on Spinoza - teens and power of these diseases in their lives in "Education Program Full Time" at the Municipal School of Basic Education Prezideu Amorim the city of Vitória - Holy Spirit. This was a qualitative study from the perspective of cartographic inspiration schizoanalysis. We used the Esquizodrama, a line of Institutionalism as trigger the creation of assemblages and devices, subjetivadas on ways of being and becoming. We sought to understand the affects that which is seen, the student, teen public school located in the suburbs, stigmatized by prejudice, discriminated and excluded from many opportunities; immersed in the scenario of violence that is called today as school bullying, and we treat how bad encounters. The violence does not happen only in this defined area, it reverberates in the surroundings, in outside school, causing a succession of dispersion and bad encounters with these students put reality. Through the thought of Spinoza, Deleuze, Guattari and Baremblitt, we sought to understand the good and bad meetings - an intervention in school - focusing on the virtues and good meetings. As devices for the production of the material used were monitored visits, participant observation, field journal, photos, pictographs, workshops tell historical Esquizodrama, clothesline banners of emotions. We note the importance of scaling up actions like this, as well as training people who can master these devices to empower and create favorable conditions for empowerment of adolescent life, enabling increasingly good meetings. Opened a possibility, their being in school, with their peers, their peers and individuals.